DNA methylation, histone acetylation in the regulation of memory and its modulation during aging - Singh, Padmanabh; Paramanik, Vijay (Frontiers in Aging, 2025)
Memory formation is associated with constant modifications of neuronal networks and synaptic plasticity gene expression in response to different environmental stimuli and experiences. Dysregulation of synaptic plasticity gene expression affects memory during aging and neurodegenerative diseases. Covalent modifications such as methylation on DNA and acetylation on histones regulate the transcription of synaptic plasticity genes. Changes in these epigenetic marks correlated with alteration of synaptic plasticity gene expression and memory formation during aging. These epigenetic modifications, in turn, are regulated by physiology and metabolism. Steroid hormone estrogen and metabolites such as S-adenosyl methionine and acetyl CoA directly impact DNA and histones’ methylation and acetylation levels. Thus, the decline of estrogen levels or imbalance of these metabolites affects gene expression and underlying brain functions. In the present review, we discussed the importance of DNA methylation and histone acetylation on chromatin modifications, regulation of synaptic plasticity gene expression and memory consolidation, and modulation of these epigenetic marks by epigenetic modifiers such as phytochemicals and vitamins. Further, understanding the molecular mechanisms that modulate these epigenetic modifications will help develop recovery approaches.